If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3 = 3x + -1 Reorder the terms: 3 + 7x = 3x + -1 Reorder the terms: 3 + 7x = -1 + 3x Solving 3 + 7x = -1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 7x + -3x = -1 + 3x + -3x Combine like terms: 7x + -3x = 4x 3 + 4x = -1 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 4x = -1 + 0 3 + 4x = -1 Add '-3' to each side of the equation. 3 + -3 + 4x = -1 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = -1 + -3 4x = -1 + -3 Combine like terms: -1 + -3 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| 4x+2-7(x+1)=6x+2 | | (4-4)x=(3+5)x | | .25x^2=36 | | 6x^2=225*24 | | -5z+7z=5z-4+6z | | 2v-40=6(v-8) | | -22=-5/8(176/5) | | X/90 | | -3x-y+3=0 | | 7(5x+1)=2x-9x | | 3y+30=2y+35 | | 19x-2=13x-32 | | (6x^3-x^2+3x)-(2x^3+5x^2+x)=0 | | ln(2)+ln(x+8)=ln(19) | | 2x-3+2x-3=x+3 | | 4(2x+9)=-22+18 | | 5x+23=3x+21 | | x^2+4x+13x=0 | | 1/4y-4=-3 | | 2(x-0)=-18 | | x^5-4x^4+3x^3= | | V=w*-2w | | -4(-2y+9)=-4 | | 7x-3x+2=x-4+6 | | f(x)=(x-5)(x-5i)(x+5i) | | 3(x-2)=-2(x+8) | | 40+x=3x | | -3(x-3)=-12 | | 2(x-2)-3=-3 | | -2+6x^2-4x=0 | | a1/2/a^2 | | 2(-2y-10)=36 |